Youth-Therapist and Parent-Therapist Match and Mismatch on Internalizing and Externalizing Treatment Goals as Predictors of Treatment Engagement - May Yeh; Devynne Diaz; Argero Zerr; Alisandra Macias; Kristen McCabe (MDPI AG, 2023)
Therapist-client cognitive match upon key constructs such as treatment goals is purported to be an important component of culturally competent care. For adolescent clients, treatment may involve both youths and their parents, suggesting the need to consider both youth-therapist and parent-therapist perspectives. This longitudinal study examined broadband youth-therapist and parent-therapist treatment goal matching and mismatching in relationship to treatment engagement in a culturally diverse sample of 245 outpatient mental health service-using youth. Although goal matching/mismatching did not uniformly predict treatment engagement as measured by a total score, youth-therapist internalizing goal matching predicted better youth engagement, and parent-therapist externalizing goal mismatch marginally predicted worse parent engagement. When selected post hoc analyses examined relationships to four individual engagement dimensions, youth-therapist internalizing goal matches positively predicted youth Client-therapist interaction, Communication/Openness, Client's perceived usefulness of therapy, and Collaboration with treatment, while parent-therapist externalizing goal mismatch negatively predicted parent Collaboration with treatment. Findings support the importance of cognitive match on treatment goals as well as the consideration of both parent and youth perspectives, matched and mismatched goals, internalizing and externalizing goals, and examining individual dimensions in addition to total scores of engagement.